2014
DOI: 10.4238/2014.september.26.6
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of CEACAM6 associated with the tumorigenesis and progression in gastric adenocarcinoma

Abstract: ABSTRACT. Carcinoembryonic antigen-related cellular adhesion molecule 6 (CEACAM6) is a member of the immunoglobulin superfamily and has been recently reported to affect the neoplastic, metastatic, and invasive ability of malignant cells by regulating intracellular signaling pathways during tumorigenesis and progression. We investigated the expression and amplification of CEACAM6 in relation to the clinicopathological and biological significance of gastric adenocarcinoma. Expression of CEACAM6 mRNA in 75 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Screening for new oncogenes and studying their mechanisms of action have important clinical diagnostic value for the early diagnosis of biomarkers and potential molecular therapeutic targets for GC. The metastasis of GC is a multi-step pathological process involving a loss of epithelial properties, such as reduced expression of E-cadherin, and a gain in mesenchymal phenotypes, such as enhanced expression of N-cadherin and vimentin (16). On one hand, tumor cells regulate the changes of their own molecules, so that they can develop in the direction of metastasis; on the other hand, they interact with other cells to form a special metastatic microenvironment and promote liver metastasis of GC (17).…”
Section: Discussionmentioning
confidence: 99%
“…Screening for new oncogenes and studying their mechanisms of action have important clinical diagnostic value for the early diagnosis of biomarkers and potential molecular therapeutic targets for GC. The metastasis of GC is a multi-step pathological process involving a loss of epithelial properties, such as reduced expression of E-cadherin, and a gain in mesenchymal phenotypes, such as enhanced expression of N-cadherin and vimentin (16). On one hand, tumor cells regulate the changes of their own molecules, so that they can develop in the direction of metastasis; on the other hand, they interact with other cells to form a special metastatic microenvironment and promote liver metastasis of GC (17).…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that CEACAM6 expression was higher in pancreatic cancer with low differentiation than in medium differentiation, similarly, it was found that CEACAM6 expression was higher in tumor tissues than in adjacent normal tissues in colon cancer (31). An increasing number of studies have found that CEACAM6 plays an important role in GC progression and that it is a prognostic biomarker and potential therapeutic target for GC (32,33).…”
Section: The Ceacam6 -Mab-irdye800cw Can Track the Tumor As Well As Metastases In Vivomentioning
confidence: 88%
“…To our knowledge, our publication is the first report on CEACAM6 blood serum expression as a statistically significant PDAC prognostic biomarker. As CEACAM6 has universal oncogenic features, it has been reported as a relevant prognostic biomarker in other malignancies: cholangiocarcinoma, osteosarcoma, renal cancer, colorectal cancer, gastric cancer [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%